2006
DOI: 10.1242/dev.02656
|View full text |Cite
|
Sign up to set email alerts
|

Novel binding partners of Ldb1 are required for haematopoietic development

Abstract: Ldb1, a ubiquitously expressed LIM domain binding protein, is essential in a number of tissues during development. It interacts with Gata1, Tal1, E2A and Lmo2 to form a transcription factor complex regulating late erythroid genes. We identify a number of novel Ldb1 interacting proteins in erythroleukaemic cells, in particular the repressor protein Eto-2 (and its family member Mtgr1), the cyclin-dependent kinase Cdk9, and the bridging factor Lmo4. MO-mediated knockdowns in zebrafish show these factors to be ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
108
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(120 citation statements)
references
References 63 publications
10
108
2
Order By: Relevance
“…Regulation of ␤-Globin Induction by Ppm1b-Previous studies have demonstrated that depletion or inhibition of Cdk9 results in a specific defect in definitive hematopoiesis (35) and erythroid induction (36). This may be by virtue of the fact that Cdk9 associates in an erythroid-specific transcription complex with SCL, Ldb1, Runx1, and GATA1 (35,36).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regulation of ␤-Globin Induction by Ppm1b-Previous studies have demonstrated that depletion or inhibition of Cdk9 results in a specific defect in definitive hematopoiesis (35) and erythroid induction (36). This may be by virtue of the fact that Cdk9 associates in an erythroid-specific transcription complex with SCL, Ldb1, Runx1, and GATA1 (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…This may be by virtue of the fact that Cdk9 associates in an erythroid-specific transcription complex with SCL, Ldb1, Runx1, and GATA1 (35,36). In addition, Cdk9 localization to the murine ␤-globin promoter and coding region increases when MEL cells are induced to terminally differentiate (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single-stranded DNAbinding protein 2 increases steady-state levels of endogenous Ldb1 and LMO2, GATA-E-box DNA binding activity, and facilitates expression of a direct target of the GATA-E-box-binding complex Protein 4.2 (P4.2) in erythroid precursor cells (Xu et al, 2007). Proteomic studies identified Eto-2 and cyclin-dependent kinase Cdk9 as Ldb1-interacting proteins (Meier et al, 2006). Ldb1 forms multiple complexes during erythroid differentiation, and morpholino-dependent knockdown of these components in zebrafish revealed that they are essential for definitive hematopoiesis (Meier et al, 2006).…”
Section: Scl (Tal-1)mentioning
confidence: 99%
“…Proteomic studies identified Eto-2 and cyclin-dependent kinase Cdk9 as Ldb1-interacting proteins (Meier et al, 2006). Ldb1 forms multiple complexes during erythroid differentiation, and morpholino-dependent knockdown of these components in zebrafish revealed that they are essential for definitive hematopoiesis (Meier et al, 2006). SCL activity is regulated via standard mechanisms involving post-translational modifications and interactions with coregulators, although many questions remain unanswered regarding the precise mechanisms.…”
Section: Scl (Tal-1)mentioning
confidence: 99%